Explore the Anti-Acne Mechanism of Licorice Flavonoids Based on Metabonomics and Microbiome - Ruan, Shi-Fa; Hu, Yi; Wu, Wen-Feng; Du, Qun-Qun; Wang, Zhu-Xian; Chen, Ting-Ting; Shen, Qun; Liu, Li; Jiang, Cui-Ping; Li, Hui; Yi, Yankui; Shen, Chun-Yan; et al. (Frontiers in Pharmacology, 2022)
Acne vulgaris is a common chronic inflammatory skin disease, and it was prone to a variety of lesions. Although in previous studies, we had found that licorice flavonoids (LCF) play an anti-acne role by inhibiting PI3K-Akt signaling pathways and mitochondrial activity, the mechanism of LCF regulating skin metabolism, serum metabolism and skin flora is still unclear. Here, we performed a full spectrum analysis of metabolites in the skin and serum using UHPLC-Triple TOF-MS. The results showed that LCF could treat acne by regulating the metabolic balance of amino acids, lipids and fatty acids in serum and skin. Similarly, we performed Illumina Hiseq sequencing of DNA from the skin flora using 16S ribosomal DNA identification techniques. The results showed that LCF could treat acne by regulating the skin flora to interfere with acne and make the microecology close to the normal skin state of rats. In summary, this study confirmed the anti-acne mechanism of LCF, namely by regulating metabolic balance and microbial balance. Therefore, this discovery will provide theoretical guidance for the preparation development and clinical application of the drug.